Strategi Pembelajaran Bahasa Arab Di ITC (Islamic Training Center) Pare - Ratna Sa’idah (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2016)
One of non-formal institution which applies Arabic learning practice method is Islamic Training Center (ITC), an Arabic course institution standardized the Middle East by using EL-BARQIE (special method without formula). ITC uses motto 5 in 1 including Qowa’id ‘Arabiyyah Shamilah, Qira’ah, Kitabah, Tarjamah, Muhadathah, and Ta’bir. This institution is located in Jl. Brawijaya 16 Singgahan, beside ITC mosque Pelem, Pare, Kediri. This research aims at investigating Arabic learning system in Islamic Training Center (ITC) Pare, and the outcome of the students in learning Arabic language in that institution. The finding shows that the special characteristic of ITC that is different with the others is the Middle East standard which can be seen in (1) the accent used in learning Arabic language which always uses lahjah Arabian, especially when takallum. (2) tarkib al-kalimah / sentence pattern used in Arabic language either takallum, qira’ah or kitabah must use Arabian pattern/tarkib Arab fushha, preposition, muta’addi sentence, not Indonesian pattern, but Arabian pattern. (3) Learning materials which are sourced from Al-Qur’an and Hadist are always directed to guidance of learning Islamic study as well written ITC (Islamic Training Center) Pare for Islamic Guidance.